Answer:
See below
Step-by-step explanation:
Let the function be quadratic as the given points are not collinear, not a linear function
<u>Standard form of quadratic equation:</u>
<u>Substituting the coordinates, we get:</u>
- 13 = a(6)^2 + b(6) + c
- -10 = a(10)^2 + b(10) + c
- 5 = a(0)^2 + b(0) + c
<u>From equation 3 we get c = 5, considering this in the other equations and simplifying:</u>
- 13 = 36a + 6b + 5 ⇒ 36a + 6b = 8 ⇒ 18a + 3b = 4
- -10 = 100a + 10b + 5 ⇒ 100a + 10b = -15 ⇒ 20a + 2b = -3
<u>Subtract 3 times the second equation from 2 times the first:</u>
- 2(18a) + 2(3b) - 3(20a) - 3(2b) = 4(2) - 3(-3)
- 36a - 60a = 8 + 9
- -24a = 17
- a = - 17/24
<u>Finding the value of b:</u>
- 18(-17/24) + 3b = 4
- 3b = 4 + 51/4
- b = 67/12
<u>The quadratic function is:</u>
- y = -17/24x^2 + 67/12x + 5
<u>So the graph of any polynomial function:</u>
- y = -17/24x^2 + 67/12x + 5 + g(x)(x-6)(x-10)(x-0)
will pass through the given 3 points